Delay in consulting a medical practitioner about rectal bleeding. Issue 3 (June 1992) - Byles, J E; Redman, S; Hennrikus, D; Sanson-Fisher, R W; Dickinson, J
Abstract : STUDY OBJECTIVE--The aims were to estimate the incidence of rectal bleeding in the community, and to determine the proportion of individuals who delay or fail to seek medical advice after a first episode of rectal bleeding. DESIGN--The data were collected as part of a large scale general population survey of the health practices and attitudes of individuals in a randomly selected sample of 2121 households. SETTING--The survey was conducted in the Newcastle and Lake Macquarie areas of New South Wales, Australia, during 1987-88. PARTICIPANTS--Information about rectal bleeding was collected from 1213 individuals aged 40 years and over. MEASUREMENTS AND MAIN RESULTS--Of the 1213 people aged 40 years and over, 239 (20%) reported noticing rectal bleeding at some time in their life. However, since an estimated 4.5% had noticed rectal bleeding for the first time in the past year the true lifetime incidence of rectal bleeding is likely to be much higher. Of the 77 individuals who had noticed a first occurrence of rectal bleeding more than three months but less than five years prior to the interview, 23 (30%) had either not sought medical advice or had only done so after a period of delay. The most commonly reported reason for delay or failure to consult was thinking that the bleeding was not serious and would clear up by itself. CONCLUSIONS--The data suggest that prompt investigation of rectal bleeding is not occurring in a relatively large proportion of cases. However, in the absence of firm evidence that early detection improves prognosis, and considering the costs of screening, it would be premature to initiate programmes which encourage people to seek care promptly for this symptom.